Thinking in numbers : on life, love, meaning, and math - Tammet, Daniel, 1979- (New York : Little, Brown and Company, 2013)
The book that Daniel Tammet, bestselling author and mathematical savant, was born to write. In Tammet's world, numbers are beautiful and mathematics illuminates our lives and minds. Using anecdotes, everyday examples, and ruminations on history, literature, and more, Tammet allows us to share his unique insights and delight in the way numbers, fractions, and equations underpin all our lives. His idiosyncratic worldview gives us new perspectives on the universal questions of what it is to be human and how we make meaning. This book will change the way you think about math and fire your imagination to see the world with fresh eyes.--From publisher description.
Family values -- Eternity in an hour -- Counting to four in Icelandic -- Proverbs and times tables -- Classroom intuitions -- Shakespeare's zero -- Shapes of speech -- On big numbers -- Snowman -- Invisible cities -- Are we alone? -- The calendar of Omar Khayyam -- Counting by elevens -- The admirable number of Pi -- Einstein's equations -- A novelist's calculations -- Book of books -- Poetry of the primes -- All things are created unequal -- A model mother -- Talking chess -- Selves and statistics -- The cataract of time -- Higher than heaven -- The art of math.
Keywords: Mathematics -- Popular works; Mathematics -- Social aspects; Asperger Syndrome; Mathematics; Mathematics; Mathematics -- Social aspects; Savant-Syndrom; Unterhaltungsmathematik; Mathematik; Mathematics; Mathematics -- Social aspects; Nonfiction; Popular works